Nanotoxicity to agroecosystem: impact on soil and agriculture - Mahendra Rai; Aniket Gade; Ingle, A. P; Indarchand Gupta; Raksha Pandit; Santos, C. A. dos (Emerging Trends in Agri-Nanotechnology, 2018)
This chapter discusses the potential impacts of nanomaterials on the agroecosystem. It highlights how the potential widespread use of nanomaterials in agriculture could have negative impacts on the agroecosystem- e.g., through alterations in the soil constituents and the microflora. It also highlights that the available information so far on this subject is limited and that extensive studies would be needed to fully understand the biochemical, physiological and molecular mechanisms for the interaction of nanoparticles with plants.